2004
DOI: 10.1523/jneurosci.1319-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Self-Administration of Ethanol within the Ventral Tegmental Area of Male Wistar Rats: Evidence for Involvement of Dopamine Neurons

Abstract: Previous work from our laboratory indicated that female Wistar rats will self-administer ethanol (EtOH) directly into the posterior ventral tegmental area (VTA). These results suggested that VTA dopamine (DA) neurons might be involved in mediating the reinforcing actions of EtOH within this region. The objectives of this study were to determine (1) the dose-response effects for the self-administration of EtOH into the VTA of male Wistar rats, and (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
191
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 182 publications
(211 citation statements)
references
References 40 publications
18
191
1
1
Order By: Relevance
“…Although not systematically studied, the estrous cycle did not appear to significantly alter self-administration behavior, as indicated by fairly stable responding across several sessions, when the same concentration of EtOH (RoddHenricks et al, 2003) or ACD (Rodd-Henricks et al, 2002b) was given. Furthermore, a significant gender effect for the self-infusion of EtOH was not observed in a recent study using male Wistar rats (Rodd et al, 2004b).…”
Section: Animalsmentioning
confidence: 71%
See 4 more Smart Citations
“…Although not systematically studied, the estrous cycle did not appear to significantly alter self-administration behavior, as indicated by fairly stable responding across several sessions, when the same concentration of EtOH (RoddHenricks et al, 2003) or ACD (Rodd-Henricks et al, 2002b) was given. Furthermore, a significant gender effect for the self-infusion of EtOH was not observed in a recent study using male Wistar rats (Rodd et al, 2004b).…”
Section: Animalsmentioning
confidence: 71%
“…Local administration of triazole as opposed to peripheral injection was used for a combination of reasons. Our previous success with coinfusing quinpirole (Rodd et al, 2004b) or 5-HT 3 antagonists (Rodd-Henricks et al, 2003) suggested that a local pharmacological effect for blocking the actions of EtOH could be obtained with this approach. Triazole is an irreversible inhibitor (reviewed in Hunt, 1996;Smith et al, 1997) and should produce progressive inhibition of intracellular catalase activity around the injection site during each of the 4-h sessions.…”
Section: General Test Conditionmentioning
confidence: 99%
See 3 more Smart Citations